10.1016/s1541-9800(09)70053-5 (CrossRef Listing of Deleted DOIs, 2000)
High-grade serous ovarian carcinoma (HGSOC) frequently recurs after platinum-taxane therapy, yet recurrence-associated changes within ascites remain unclear. We performed cell-type-resolved quantitative proteomics on paired ascites samples collected at primary diagnosis and at disease recurrence from three HGSOC patients, profiling unsorted cells alongside matched CD45- tumor-enriched and CD45+ immune-enriched fractions. Conventional proteomic label-free quantitative (LFQ) analysis yielded limited significant proteins due to inter-patient heterogeneity. To address this, we applied Gene Set Enrichment Analysis (GSEA) to identify coordinated pathway-level alterations associated with recurrence. Across all cellular compartments, recurrent samples exhibited consistent downregulation of interferon-α/γ-associated pathways alongside enrichment of oxidative phosphorylation and stress-adaptive metabolic programs. In the CD45+ immune compartment, these changes were accompanied by enhanced IL-2/STAT5 signaling and reduced antigen-presentation pathways. Together, these findings suggest that recurrent ascites is characterized by a shift toward oxidative metabolism and a more immunosuppressive microenvironment.